Modeling the surface mass balance of Penny Ice Cap, Baffin Island, 1959–2099 - Nicole Schaffer; Luke Copland; Christian Zdanowicz; Regine Hock (Annals of Glaciology)
Glaciers of Baffin Island and nearby islands of Arctic Canada have experienced rapid mass losses over recent decades. However, projections of loss rates into the 21st century have so far been limited by the availability of model calibration and validation data. In this study, we model the surface mass balance of the largest ice cap on Baffin Island, Penny Ice Cap, since 1959, using an enhanced temperature index model calibrated with in situ data from 2006–2014. Subsequently, we project changes to 2099 based on the RCP4.5 climate scenario. Since the mid-1990s, the surface mass balance over Penny Ice Cap has become increasingly negative, particularly after 2005. Using volume–area scaling to account for glacier retreat, peak net mass loss is projected to occur between ~2040 and 2080, and the ice cap is expected to lose 22% (377.4 Gt or 60 m w.e.) of its 2014 ice mass by 2099, contributing 1.0 mm to sea level rise. Our 2015–2099 projections are approximately nine times more sensitive to changes in temperature than precipitation, with an absolute cumulative difference of 566 Gt (90 m w.e.) between +2 and −2°C scenarios, and 63 Gt (10 m w.e.) between +20% and −20% precipitation scenarios.